ANALISIS IMPAS SEBAGAI DASAR PENGAMBILAN KEPUTUSAN MANAJEMEN DALAM PENENTUAN LUAS PODUKSI MINIMAL PADA INDUSTRI PEMINDANGAN IKAN LAUT DI DUSUN PAYANGAN WATU-ULO JEMBER - Amien Pudjanarso (RELASI : JURNAL EKONOMI, 2015)
This research was intended toanalys  the minimum  scale production  of the  sea fish preservation  industry at  Payangan  village, watu-ulo, Jember, preventing the  businessman in the sea fish preservation industry’s profit loss. Break even analized in this research are fixed cost, variable cost, price per unit, total revenue, total cost, and net sales. The population used in this researh are all of the businessman in the sea fish preservation industrial company by Payangan village, watu ulo (17 businessman). The data analysing method used in this research is  break even point.  The  result show that scale of minimum  production which  businessman must achieves.